2017
DOI: 10.1038/nm.4287
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of human APOL1 risk variants in podocytes induces kidney disease in mice

Abstract: African-Americans have an increased risk of developing chronic and end-stage kidney disease, with much of it attributed to two common genetic variants in the APOL1 gene, termed G1 and G2. Direct evidence demonstrating that these APOL1 risk alleles are pathogenic is still lacking as the APOL1 gene is only present in some primates and humans; thus experimental proof of causality of these risk alleles for renal disease has been challenging. Here, we generated mice with podocyte-specific inducible expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
403
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(438 citation statements)
references
References 47 publications
21
403
1
1
Order By: Relevance
“…Together, these results suggest that the risk variants are more likely altering a functional role of APOL1, as opposed to its cellular distribution or subcellular localization. In contrast to these results, another study showed that variant APOL1s had increased localization with RAB7-and RAB11-labeled endosomes compared with G0 in transiently transfected HEK293 cells and cultured human podocytes (24).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Together, these results suggest that the risk variants are more likely altering a functional role of APOL1, as opposed to its cellular distribution or subcellular localization. In contrast to these results, another study showed that variant APOL1s had increased localization with RAB7-and RAB11-labeled endosomes compared with G0 in transiently transfected HEK293 cells and cultured human podocytes (24).…”
Section: Discussionmentioning
confidence: 66%
“…Localization of VAMP8 with its cognate autophagosomal SNARE partner STX17 is diminished in presence of APOL1 variants (24). In addition, mice and Drosophila transgenic for human APOL1 kidney disease risk variants have been shown to have disordered endosomal trafficking and variant-dependent glomerular and nephrocyte injury (24,34,35). Our results suggest a model in which APOL1, in concert with VAMP8 or other SNARE proteins, identifies vesicles containing cargo capable of mediating cellular damage and their functional interaction mediates a cellular response capable of attenuating/mitigating the pathogenic potential of these cargos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While significant advances have been made in our understanding of APOL1 ‐associated kidney disease,14 the specific mechanisms by which these genetic variants cause kidney disease remain uncertain. Because of the elevated risks for cardiovascular disease (CVD) and heart failure (HF) among people with chronic kidney disease compared with the general population,15 investigation of the cardiovascular risk of individuals who carry the APOL1 high‐risk variants is an issue of active study.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic mice models can be generated to study the influence of relevant genes. The APOL1 gene encodes apolipoprotein L1, and variants of the gene (APOL1-G1 and -G2) are associated with kidney disease [49]. As the gene is only found in humans and some primates, transgenic mice models were developed to study the gene variants in vivo.…”
Section: Transgenic Modelsmentioning
confidence: 99%